Some Universities Performance Evaluation of Entrepreneurship and Innovation in Turkey with Multiple Criteria Decision Making Methods - Karahan, Mehmet; Peşmen, Sariye (Springer Science and Business Media Deutschland GmbH, 2021)
The concept of “Entrepreneurial and Innovative University” is frequently encountered in recent years. Innovation is becoming increasingly important for universities as well as for the regions they live in as in all areas of life. In this context, entrepreneurial and innovative university-based enterprises have become an important tool in the transfer of information and technology and in solving social problems. Student and academician mobility in universities, cross-border investments between countries and widening the scope of competition have made the change inevitable for universities to survive. This change forces universities to turn into an entrepreneurial and value-creating structure by abandoning their known education, training, and research-based structure. In the face of developments, many universities in developed countries are trying to adapt to this change and they have started to practice “entrepreneurial universities”. This change has become inevitable for the universities of our country that feel the pressure of all the global, national and institutional effects and this has started to be used as a competitive tool. In this way, it will be possible for our country to come up with a suitable model and to transform the universities of our country into efficient, innovative, transparent and quality oriented universities. In this study, firstly, the phases of change developed by considering the historical process of universities and the concepts of third generation university and entrepreneur university are explained. Identifying needs to be done to increase the universities’ entrepreneurship and innovation properties in Turkey, it is necessary to create the infrastructure for it. The entrepreneurial university paradigm to study how it works and the universities in Turkey to be able to produce some results that can be assessed how measured in this direction, that can bring a fundamental paradigm shift in the focus of university entrepreneurship makes it extremely important research. In the study, Entrepreneurial and Innovative University Index using the data of 2018, the entrepreneurship and innovation performances of the universities were analyzed with Promethee GAIA, which is one of the MCDM methods. As a result of the analysis, the criteria with the highest weight and the performance ranking of alternative universities were determined. Comparison of the top ten universities and regional universities has been made and necessary suggestions have been developed to overcome the identified positive or negative differences. © 2021, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.
International Symposium for Production Research, ISPR 2020 -- 24 September 2020 through 26 September 2020 -- Antalya -- 250869
Keywords: Entrepreneurial and innovative university; MCDM; Performance evaluation; Promethee GAIA; Third generation university